KOMPARASI SELF REGULATED LEARNING PADA MAHASISWA YANG BEKERJA DAN MAHASISWA YANG TIDAK BEKERJA - Feida Noor Laila Istia’dah (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2018)
This research is held based on the fact especially at Muhammadiyah University of Tasikmalaya there are students who choose college while working in order to continue higher education. Students who are college while working and college students who are just college (not working) in this case have the same goal of successful lectures. Self regulation learning can play a role in achievement. But in the process of achievement, students will face problems in achievement, such as expectations of low expectations of success, avoidance of failure, task delays, too perfectionistic tasks, high anxiety, and apathy toward learning at university. The purpose of this study is to determine the general picture and the difference of self-regulated learning on students who work with students who are not working FKIP Umtas students. The approach used in this research is quantitative approach with descriptive method. The sampling technique used purposive non probability sampling. The instruments used were collected through a questionnaire. The result of the research shows that General Regulated Learning of FKIP UMTAS students is in the high category with the percentage of 79.60% of the population. Based on the data analysis results obtained significance value of 0.800, more than the significance level of 0.05 then Ho accepted. This means there is no difference between working with the unemployed. This means that students who work have Self Regulated Learning that is not different from students who do not work.